Penerapan Articial Intelligence sebagai Stimulus Niat Beli Konsumen dalam Pemasaran Media Sosial - Kusuma, Pradana Jati; Purusa, Nanda Adhi; Aqmala, Diana; Chasanah, Amalia Nur (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Artificial intelligence technology offers accuracy and efficiency in the online shopping experience on social media. The experience of social media users who have applied artificial intelligence can optimize the other potentials of social media. This research presents the application of artificial intelligence technology through accurate experiences and interactive experiences with utilitarian value as a mediating variable that drives consumer purchase intentions. The accuracy of experience and the interactive experience in utilizing artificial intelligence on social media has a significant direct and indirect influence on consumer purchasing intentions. However, perceived utilitarian value can encourage consumer purchases better than the experience of directly implementing artificial intelligence technology. The results of this research show that the accuracy and interaction of artificial intelligence technology on social media are able to encourage the formation of consumer purchase intention